Implementasi Clean Code Berdasarkan Smells and Heuristics Aplikasi MDP SIGN - Kurniawan, Wiji; Widhiarso, Wijang; Rachmadi, Muhammad (Universitas Multi Data Palembang, 2024)
This research explores the analysis of the MDP SIGN application by applying clean code principles based on code smells and heuristics. The main focus of clean code, which emphasizes writing code that is easy to understand, is key for efficient maintenance and team collaboration. Code smells, as indicators of code structure issues, and heuristics as rules of thumb, became the basis for analyzing this application. The refactoring process was applied to MDP SIGN, a QR code-based digital signing application. The analysis identified potential improvements by finding code smells such as N1: Choose Descriptive Names, N4: Unambiguous Names, G5: Duplication, F4: Dead Function, and C5: Commented-Out Code. Through the implementation of clean code, the author managed to reduce 330 lines of code and improve efficiency. Validation involved the original developer, improving understanding of the code. This research contributes to the practical understanding of the application of clean code in application development.